The Genomic Profile of Pregnancy-Associated Breast Cancer: A Systematic Review - Korakiti, Anna-Maria; Moutafi, Myrto; Zografos, Eleni; Dimopoulos, Meletios-Athanasios; Zagouri, Flora (Frontiers in Oncology, 2020)
Breast cancer is the most common malignancy diagnosed during pregnancy. Strong data on the genomic profile of pregnancy-associated breast cancer are lacking. This systematic review aims to integrate and analyze all existing data from the literature regarding the genomic background and the gene mutational patterns of pregnancy-associated breast cancer. Using various genomic analysis methods, multiple differentially expressed genes and numerous non-silent mutations have been detected. More particularly, our review demonstrates the aberrant expression of several oncogenes (e.g. MYC, SRC, FOS), tumor suppressor genes (e.g. TP53, PTEN, CAV1), apoptosis regulators (e.g. PDCD4, BCL2, BIRC5), transcription regulators (e.g. JUN, KLF1, SP110), genes involved in DNA repair mechanisms (e.g. Sig20, BRCA1, BRCA2, FEN1), in cell proliferation (e.g. AURKA, MKI67), in the immune response (e.g. PD1, PDL1) and in other significant biological processes (e.g. protein modification, internal cell motility). Further research on the genomic profile of pregnancy-associated breast cancer is urgently required in order to identify potential biomarkers facilitating early-stage diagnosis and individualized therapy.